Effect of Governance and Social Sustainability Reporting on the Financial Performance of Listed Manufacturing Firms in Nigeria - Omotoso, Akorede; Yusuf , Mohammed Aliyu; Idris, Adamu Adamu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The study investigated the effect of governance and social sustainability reporting on the financial performance of listed manufacturing firms in Nigeria. The study covered a sample of 32 listed manufacturing firms in Nigeria from 2014 to 2021. The descriptive statistics and the pool OLS with robust standard error estimation technique were used to analyze the data. The result showed that governance reporting has significant effect on financial performance; also, social reporting has a negative significant effect on financial performance. The implication of this finding underscores the value of strong governance frameworks in enhancing investor confidence and ensuring effective management, which collectively contribute to better financial performance. The study recommends that manufacturing firms should prioritize strengthening their governance reporting practices as transparent and effective governance mechanisms can lead to enhanced financial performance and greater trust from investors and also assess their social reporting strategies and expenditures.